ʺEducation of civic position of cadets in military higher educational institutions: theoretical aspectʺ - Baglay, M. (Problems of Engineer-Pedagogical Education, 2024)
The article reveals the problem of educating the civic position of cadets - future officers, which is relevant in the light of modern military events related to aggression from a neighboring state. It is emphasized that scientific and pedagogical understanding of ways to develop citizenship acquires special importance in military institutions of higher education, which have accumulated rich experience in developing civic qualities in cadets. It is noted that the level of formation of the civil position of his subordinates, as well as subsequent generations of military personnel, largely depends on the patriotic and civic position of the cadet - the future officer of a military institution of higher education, because the officer performs the functions of a leader and mentor when cadets solve official and combat training tasks for the protection of the state, a teacher and educator who helps cadets form a civic position and patriotic qualities. The concept of “civic position” is defined as a complex of spiritual and moral attitudes and experiences of the individual for the fate of the Motherland, manifested in a culture of feelings, moral feelings, a sense of patriotism, national cultural identity, civic dignity, civic responsibility, civic duty of conscience, civic courage, respectful attitude and love for the Motherland, which is reflected in socially significant actions, actions aimed at ensuring social interests and human rights, as well as changing the social environment in accordance with moral values and current social objectives;